Row orientation and weeding time effect on yield of Aman rice (Bangladesh Journal of Scientific and Industrial Research, 2021)
The effect of row orientation and weeding time on growth, yield and yield attributes of transplanted Aman (T. Aman) rice cv. BRRI dhan41 were tested in the agronomy field laboratory of the Bangladesh Agricultural University, Mymensingh. The experiment was carried out from July to December 2017. It comprised three row orientations viz. east-west, north-south and haphazard planting, and four weeding times viz. no weeding, weeding at 20 days after transplanting (DAT), weeding at 40 DAT and weeding at 60 DAT. Plant height, total tillers per hill, effective tillers per hill, grains per panicle, grain and straw yields were greater in east-west and north-south row orientation than in haphazard planting being the highest in east-west row orientation. But within east-west and north-south row orientation, there was no significant difference on plant characters. The highest performance in yield attributes and yield was observed in weeding at 40 DAT and the lowest one was recorded in no weeding. Among the treatment combinations, the highest yield was observed in east-west row orientation with weeding at 40 DAT for BRRI dhan41.Bangladesh J. Sci. Ind. Res.56(1), 47-52, 2021